CONDITION OF COMMUNITY LIVELIHOOD ASSETS AROUND MUHAMMADIYAH'S CHARITY BUSINESS TOWARDS SUSTAINABLE LIVELIHOODS DURING COVID 19 IN TALIWANG, WEST SUMBAWA - Ibrahim Ibrahim (JURNAL GEOGRAFI, 2022)
Various covid-19 period programs have not made the community empowered and independent. The development of the Muhammadiyah Business Charity (AUM) program in the movement is still low in West Sumbawa Regency. Have various livelihood strategies in the surrounding community. This study aims to examine the condition of the livelihood assets of the community around AUM towards sustainable livelihoods during the Covid 19 period in Taliwang, West Sumbawa. The method used in this research is descriptive. The study results indicate that the community's livelihood assets around AUM are; first, human capital is more dominant in Lenang Late Village, reaching an average of 53.46; secondly, natural capital is more prevalent in Brang Bulu Hamlet, reaching an average of 2.58. The physical means of the three hamlets have the same average level going 18. Fourth, social capital is more dominant in Dusun Brang Pandan, reaching an average of 38.64; fifth, financial wealth is more prevalent in Dusun Lenang Late, reaching an average of 21.92. The level of community livelihoods at the Branch and Subdistrict levels during the Covid-19 period had various assets, but strategic measures were needed to ensure a better and sustainable livelihood.Keywords: Asset, Muhammadiyah Business Charity, and Covid-19.